Isolation and Characterization of Bacillus thuringiensis From Various Habitats in Five Locations in the Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
In a study aiming at the isolation and characterization ofBacillus thuringiensis (B.t.) strains from five localities in the Sudan,biochemical characterization revealed that nine of the 33 isolatesexhibited typical B.t. biochemical characteristics, eleven showeddeviation in only one biochemical trait and 13 showed deviation in two ormore characteristics. Serological characterization of the isolates againstthree imported reference B.t. subspecies by agglutination tests showedthat eight of the isolates were positively agglutinated by the anti-kurstakiserum, three by the anti-israelensis serum and two by the anti-tenebrionisserum. The remaining 20 isolates were untypable by any of the threeantisera that were used. The use of these isolates as biocontrol agentsagainst insect pests is discussed.
Keywords: Bacillus thuringiensis; agglutination; serotypes; Sudan